Manufacturing Industry Business Marketing Strategy at PT Segawan Solo - Burhan Stafrezar (PT. Putra Jawa Mulya ( Putra Jawa Publisher ), 2024)
This research aims to analyze the marketing strategy implemented by PT Segawan Solo, a company operating in the manufacturing industry. The main focus of this research is to understand how the marketing strategy implemented can influence company performance, especially in the face of increasingly tight market competition. This research uses a qualitative approach with a case study method, which involves in-depth interviews with marketing management, direct observation of marketing activities, and analysis of secondary data from company reports. The research results show that PT Segawan Solo implements an integrated marketing strategy, including digital marketing via social media, improving product quality, price adjustments, and expanding the distribution network. Product innovation and adaptation to market trends are the main drivers for the success of this marketing strategy. The conclusions of this research indicate that adaptive and data-based marketing strategies can help PT Segawan Solo increase its market share and competitiveness in the manufacturing industry.